The roles of astrocyte in the brain pathologies following ischemic stroke. (12th May 2019) - Sun, Linlin; Zhang, Yixuan; Liu, E; Ma, Qingyi; Anatol, Manaenko; Han, Hongbin; Yan, Junhao
ABSTRACT: Aim : In this work, we systematically explored the physiological functions of astrocytes and their roles following ischemic stroke, additionally, the potential therapy strategy targeting the astrocytes was also discussed. Methods : This work searched the PubMed database (including MEDLINE) until 14 Feb 2018, and furthermore, the studies were identified through cross-referencing and by consulting the experts in this field. Results : This study indicated that the astrocytes can not only play harmful roles following ischemic stroke through release of inflammatory factors and formation of glial scar but also have protective effects through quenching glutamate excitotoxicity and maintaining the clearance function of glymphatic system in brain. Conclusion : Owing to their important roles in physiological functions of brain and in the pathological conditions following ischemic stroke, the astrocytes might be a potential but promising therapeutic target for treating the ischemic stroke in the future.